Association of novel characterized sequence variations in the ζ-carotene desaturase (Zds) gene with yellow color and yellow pigment content in durum wheat cultivars. (May 2021) - Pasten, María Cielo; Roncallo, Pablo Federico; Camargo Acosta, Emily Yineth; Echenique, Viviana; Garbus, Ingrid
Abstract: In durum wheat ( Triticum turgidum L. var. durum ), grown primarily for the production of pasta and other food products, yellow color is an important quality standard. This trait is linked to several different aspects, such as processing conditions, degradation by enzymes, environmental factors and, most importantly, the natural concentration of yellow carotenoid pigments. One of the crucial phases in the carotenoid biosynthesis pathway is carotene desaturation, and it is catalyzed by two desaturases: Phytoene desaturase (PDS) and ζ-Carotene desaturase (ZDS). In this study, we report the presence of two polymorphisms in the Zds genes that strongly suggest that this gene is duplicated in the durum wheat A and B genomes, providing valuable knowledge about the distribution of this gene in durum wheat germplasm. The polymorphism detected in the A genome was successfully associated with differences in the phenotypic expression of yellow pigment in 133 durum wheat cultivars, thus constituting a novel functional marker for use in breeding programs that aim to improve pasta quality and which contributes to a better understanding of the inheritance of color traits in durum wheat. Graphical abstract: Image 1 Highlights: The Zds gene is duplicated in the durum wheat A and B genomes. A 12 indel from the durum wheat A genome was associated with the phenotypic expression of yellow pigment. The developed functional marker is a helpful tool for marker-assisted selection in durum wheat breeding programs.